Answer:
(-
, 4 )
Explanation:
Given the 2 equations
3x + 8y = 28 → (1)
3x + 2y = 4 → (2)
Subtracting (2) from (1) term by term will eliminate the x- term
(3x - 3x) + (8y - 2y) = (28 - 4), that is
6y = 24 ( divide both sides by 6 )
y = 4
Substitute y = 4 into either of the 2 equations and solve for x
Substituting into (1)
3x + 8(4) = 28
3x + 32 = 28 ( subtract 32 from both sides )
3x = - 4 ( divide both sides by 3 )
x = -
![(4)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v06kk866m9eblk3tmf1mug5xdc1z0o4ea5.png)
Solution is (-
, 4 )